Analysis of Dilatometry Data of the Stainless Steel 316L Bimodal Powder Sintering Process; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Rodkevich N. Nikolay; Glazkova E. Elena; Pervikov A. Aleksandr; Lerner M. I. Marat Izrailyevich; Kazantsev S. Sergey (2018, 2018)
Title screen